2001
DOI: 10.1152/jn.2001.85.4.1661
|View full text |Cite
|
Sign up to set email alerts
|

Slow and Fast (Gamma) Neuronal Oscillations in the Perirhinal Cortex and Lateral Amygdala

Abstract: Most lesion studies emphasize the distinct contributions of the amygdala and perirhinal cortex to memory. Yet, the presence of strong reciprocal excitatory projections between these two structures suggests that they are functionally coupled. To gain some insight into this issue, the present study examined whether the close anatomical ties existing between perirhinal and lateral amygdala (LA) neurons are expressed in their spontaneous activity. To this end, multiple simultaneous recordings of single unit discha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
50
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(59 citation statements)
references
References 77 publications
(62 reference statements)
8
50
0
1
Order By: Relevance
“…The LFP activity pattern mirrored that of neuronal firing in each region such that the initial negative deflection in potential coincided with neuronal bursting in mPFC and BLA. This temporal association between unit and LFP activity has been reported previously in both cortical and amygdaloid regions (Collins et al, 2001;Steriade, 1997). It should be noted that the low frequency LFP activity seen under basal conditions and in response to vehicle is not due to true slow wave oscillations but rather to the \average" of high frequency activity of short duration and the very low activity periods of longer duration observed during the 150 s epoch.…”
Section: Resultssupporting
confidence: 84%
“…The LFP activity pattern mirrored that of neuronal firing in each region such that the initial negative deflection in potential coincided with neuronal bursting in mPFC and BLA. This temporal association between unit and LFP activity has been reported previously in both cortical and amygdaloid regions (Collins et al, 2001;Steriade, 1997). It should be noted that the low frequency LFP activity seen under basal conditions and in response to vehicle is not due to true slow wave oscillations but rather to the \average" of high frequency activity of short duration and the very low activity periods of longer duration observed during the 150 s epoch.…”
Section: Resultssupporting
confidence: 84%
“…Our hippocampal CSD, EC field and EC multiunit recordings implicate the temporo-ammonic pathway (EC layer III to the apical dendritic zone of CA1, i.e., SLM) as providing robust, rhythmic, excitatory input at slow frequencies during the SO. In support of this, the SO has been noted previously in the EC of both the ketamine-xylazine anesthetized and naturally sleeping cat (Collins et al, 1999(Collins et al, , 2001 as well as the urethane-anesthetized rat (Isomura et al, 2005). Furthermore, preliminary evidence from our laboratory (Dickson et al, 2005) suggests that lesions of the perforant pathway also affect the hippocampal SO.…”
Section: Coordination Of the Hippocampal And Neocortical Slow Oscillasupporting
confidence: 61%
“…Given that these strong connections are clustered, and the highly nonrandom nature of synaptic connectivity, it is conceivable that pyramidal neurons with strong connections may be the recipient of suprathreshold AAC excitation. This provides an ideal mechanism for the rapid activation of large numbers of pyramidal neurons, as occurs in the transition from a hyperpolarized network Down state to the depolarized Up state (Steriade et al, 1993;Cossart et al, 2003;Haider et al, 2006), a phenomenon that has been observed not only in the cortex but also in the amygdala (Collins et al, 2001).…”
Section: Discussionmentioning
confidence: 99%